Novel thawing method of ultrasound-assisted slightly basic electrolyzed water improves the processing quality of frozen shrimp compared with traditional thawing approaches - Yufeng Li; Jinsong Wang; Qiao-Hui Zeng; Langhong Wang; Jing Jing Wang; Shaojie Li; Jiahui Zhu; Xin-An Zeng (Ultrasonics Sonochemistry, 2024)
Thawing is the primary step in handling frozen aquatic products, which directly determines their end-product quality. This study firstly constructed a novel thawing method of ultrasound-assisted slightly basic electrolyzed water (UST), and its influences on the physicochemical and histological properties of shrimp, as well as the structural of myofibrillar proteins (MPs) in shrimp were evaluated. Results indicated that the UST treatment greatly reduced 48.9 % thawing time of frozen shrimp compared to traditional thawing approaches. Meanwhile, the UST effectively decreased the generation of malondialdehyde (MDA), total volatile basic nitrogen (TVB-N), and carbonyl compounds in the thawed shrimps. In addition, it significantly preserved the elasticity and integrity of muscle fiber. Notably, the UST reduced the damage of thawing to the spatial structures of MPs, thereby greatly keeping the stability of protein. All these favorable changes maintained the water holding capacity (WHC) and quality of shrimp. Therefore, the UST is a promising non-thermal thawing technology for aquatic products.